Polar phase transitions in heteroepitaxial stabilized La0.5Y0.5AlO3 thin films. (1st September 2017) - Liu, Shenghua; Zhang, Chunfeng; Zhu, Mengya; He, Qian; Chakhalian, Jak; Liu, Xiaoran; Borisevich, Albina; Wang, Xiaoyong; Xiao, Min
Abstract: We report on the fabrication of epitaxial La0.5 Y0.5 AlO3 ultrathin films on (001) LaAlO3 substrates. Structural characterizations by scanning transmission electron microscopy and x-ray diffraction confirm the high quality of the film with a − b + c − AlO6 octahedral tilt pattern. Unlike either of the nonpolar parent compound, LaAlO3 and YAlO3, second harmonic generation measurements on the thin films suggest a nonpolar–polar phase transition at T c near 500 K, and a polar–polar phase transition at T a near 160 K. By fitting the angular dependence of the second harmonic intensities, we further propose that the two polar structures can be assigned to the Pmc2 1 and Pmn2 1 space group, while the high temperature nonpolar structure belongs to the Pbnm space group.